Selfism, Empathy, Idealism and Ethical Decision Making in Business and Non-Business Context - Kasingku, Frisky Jeremy (Accounting and Finance Studies, 2024)
Research Aims: The purpose of this study is to examine the impact of individual personality on ethical decision-making in the business and non-business context. An individual's personality is measured using narcissism, empathy, and idealism. In addition, this study also examines the influence of idealism as a variable that moderates the relationship between narcissism and ethical decision-making. Design/methodology/approach: Causal studies are conducted to answer research problems. Furthermore, purposive sampling techniques were used to select samples to be used in this study. A total of 192 Accounting and management students were used as sample in this study. Research Findings: . As a result, narcissism, empathy, and idealism influence ethical decision-making in non-business contexts. In addition, the variable of idealism is not able to moderate the influence of narcissism on ethical decision-making. Theoretical Contribution/Originality: The result of this study may benefit the stream of literature related to ethical decision making. The result of this study may also benefit the business practice.